Sri Lankan Consumers’ Acceptance of M- Internet Services - Nawaz, Samsudeen Sabraz; Gunapalan, Selvaratnam; Haleem, A thambawa (International Journal of Psychosocial Rehabilitation, 2020)
This study mainly aims to determine the factors that drive the intention of consumers in Sri Lanka to use mobile Internet services. A through literature review was performed on the possible factors that may influence the behavioural intention of consumers including performance expectancy, effort expectancy, awareness, hedonic motivation, and social influence, all of which are presented as the study variables in the proposed conceptual framework. Data collection was carried out by posting the online survey questionnaire on Facebook and WhatsApp groups of numerous Internet users in the country. The proposed model and the developed hypotheses were tested by employing the Structural Equation Modelling using the AMOS software by IBM. The findings indicate that all the theorized factors have a significant effect on the behavioural intention of the consumers in using mobile Internet services. The findings provide valuable practical implications in driving the Sri Lankan consumers to adopt and use mobile Internet services.